2018
DOI: 10.1038/s12276-018-0120-3
|View full text |Cite
|
Sign up to set email alerts
|

A secretome profile indicative of oleate-induced proliferation of HepG2 hepatocellular carcinoma cells

Abstract: Increased fatty acid (FA) is often observed in highly proliferative tumors. FAs have been shown to modulate the secretion of proteins from tumor cells, contributing to tumor survival. However, the secreted factors affected by FA have not been systematically explored. Here, we found that treatment of oleate, a monounsaturated omega-9 FA, promoted the proliferation of HepG2 cells. To examine the secreted factors associated with oleate-induced cell proliferation, we performed a comprehensive secretome profiling o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 85 publications
1
11
0
Order By: Relevance
“…Previous studies reported cell proliferation inhibition and apoptosis induction after OA administration in carcinoma cells (Carrillo et al, 2012). In previous works unsaturated fatty acid oleate (an oleic acid-derived salt) induces (Vinciguerra et al, 2009;Park et al, 2018) or inhibits (Arous et al, 2011;Li et al, 2013) HepG2 cell proliferation in a concentration-dependent manner, with a mechanism only partially elucidated. We report here that increasing doses of OA reduce viability and increase cell death (Figure 4) in both HCC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported cell proliferation inhibition and apoptosis induction after OA administration in carcinoma cells (Carrillo et al, 2012). In previous works unsaturated fatty acid oleate (an oleic acid-derived salt) induces (Vinciguerra et al, 2009;Park et al, 2018) or inhibits (Arous et al, 2011;Li et al, 2013) HepG2 cell proliferation in a concentration-dependent manner, with a mechanism only partially elucidated. We report here that increasing doses of OA reduce viability and increase cell death (Figure 4) in both HCC cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…ERp57 expression significantly differs among HCC patients, at-risk patients and healthy individuals, thereby potentially serving as a biomarker for the early diagnosis of HCC 6 . Evidence suggests that ERp57 is overexpressed in HCC, colorectal cancer 30 and breast cancer 31 , 32 and participates in tumorigenesis and the progression of cancer 3 , 4 . ERp57 expression is associated with the metastatic capacity of cancer cells.…”
Section: Clinical Implications Of Erp57 In Cancermentioning
confidence: 99%
“…To ease the burden of cancer, current research is focusing largely on molecular preventive trials, which are regarded as the priority study type; biomarkers are key determinants of molecular prevention that allow us to evaluate the natural history of cancer as well as the efficacy and toxicity of an agent [2]. Recent research regarding the expression of endoplasmic reticulum resident protein 57 (ERp57) in tumors revealed that ERp57 expression is upregulated in various cancers and participates in cancer initiation, progression and chemosensitivity [3][4][5]. Some evidence suggests that ERp57 can serve as a potential molecular marker and therapeutic target of cancer [6].…”
Section: Introductionmentioning
confidence: 99%
“…NASH is characterized by accumulation of fat in liver cells. Oleate acid (OA), one of fatty acids that induce cellular adipogenesis, can promote the proliferation of HCC cells [42,43]. OA-induced lipid accumulation in HepG2 liver cancer cells is a well-established model for the investigation of hepatic steatosis [20].…”
Section: Oleate Acid Elevates the Expression Of Hmmr Via Cebpαmentioning
confidence: 99%